INTRODUCTION TO GLOBAL MARKETING ( PENGANTAR PEMASARAN GLOBAL ) - Suhairi Suhairi; Muslimatul Husnah; Indah Wulansari Batubara; Ahmad Ihsan Fiqih Siregar; Sophia Rahmadhani (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The development of technology, information and communication resulted in the globalization of the world which took place quickly and dynamically. Globalization brings changes in various everyday issues such as social, monetary, and cultural. Especially in the economic field which has major consequences for changes in the governance of business cooperation and competition as well as the duties of governments in various parts of the world. Therefore, this requires business people to continue to innovate in the face of increasingly fierce competition, because competition does not only come from local business competition but has penetrated world associations. The components that drive this paper are to analyze and find out the understanding and what are the scopes faced by business people in entering the world of global marketing, which is to help the world export and import between countries. This study uses a qualitative descriptive method, the method used in writing this scientific work is to use the library study method. Where researchers look for discussion material from the internet and books obtained from the official website and other supporting documents. Through this research, it is hoped that problems or obstacles from the marketing strategy used and alternative solutions to existing problems can be identified to achieve a better performance improvement.